PENGETAHUAN KESEHATAN MENTAL DAN SIKAP TERHADAP ODGJ PADA MASYARAKAT SALATIGA - Rachel Ayu Anindhita; Christiana Hari Soetjiningsih (Bajang Institute, 2023)
People with mental disorders or which happens often called ODGJ are those who have mental illness with symtoms of mental disorders. Public still discriminate, underestimate and even forget about ODGJ. It is happen caused public knowledge about mental health. This research aims to determine the relationship between public mental health knowledge and their attitudes towards ODGJ. This research took 121 Salatiga residents consisting of men and women with different ages and education levels. The measuring instrument in this study was adapted by Farida & Fitriani, mental health knowledge using the Mental Health Knowledge Questionnaire (MHKQ) scale consist of 20 items and attitudes towards mental disorders using the Community Attitude Toward the Mentally Ill (CAMI) scale with 40 items. The result of correlation used the Pearson’s product moment technique which showed a correlation r= 0.137 with a significance value of 0.100 where the value is >0.05. These results indicate that the hypothesis in this study isn’t accepted, it’s means that the higher the level of public knowledge about mental health isn’t guarantee that they will do something positively to ODGJ, and vice versa. This research also shows that the people of Salatiga have mental health knowledge and attitudes towards ODGJ in the medium category with a percentage value of 74% for mental health knowledge and 66% for attitudes towards mental disorders. The public continue to increase their mental health knowledge so they can take the right attitude towards ODGJ around them.